Aktivitas Antibakteri Ekstrak Etanol dan Destilat Jahe dan Sirih terhadap Mycoplasma gallisepticum dan Escherichia coli (ANTIBACTERIAL ACTIVITY OF ETHANOL EXTRACT AND DESTILAT OF GINGERS AND PIPER BETLES AGAINST MYCOPLASMA GALLISEPTICUM AND ESCHERICHIA CO - Rahminiwati, Min; Mustika, Aulia Andi; Zaim, Agung; Sutardi, Lina Novianti (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
Betle and ginger juice extracts have been reported to have antibacterial activity against E. coliand M. gallisepticum. However, fractionation analysis showed the have differences in their antibacterialpotency which appeared to be associated with the nature of the solvent polarity. This study wasconducted to obtain information about antibacterial activity of Piper betles and gingers extract againstE. coli and M. gallisepticum. Three types of betle, P. betle, P. betle var nigra, P. crocatum, wereexamined for their antibacterial activity using disc method and three types of ginger, Zingiber officinale,Z. officinale Linn var rubrum, and Z. majus rumph which were extracted by soxhletation using ethanol30%, 60% and 90% as well as distestillation for three and five hours. Piper betle and P. crocatumconsistently have antibacterial effect against E. coli whereas Z. officinale consistently has antibacterialeffect against M. gallisepticum, either extracted by distillation or soxhletation. Piper betle is potentialyield of distillate and extract that has the highest antibacterial activity against E. coli, and M.gallisepticum with inhibitory zone were 9.76 mm and 22 mm respectively.
Keywords: Mycoplasma gallisepticum, Piper betle, ginger, Escherichia coli